Kontribusi Aspek Hukum Ekonomi Islam dalam Perlindungan Konsumen di Indonesia - Masitoh Masitoh (Yayasan Azhar Amanaa Yogyakarta, 2023)
In the era of globalization and free trade (global market), Indonesia's economic development, especially in the field of industry and trade, has brought significant benefits to all stakeholders (employers). This means that the choice of goods and services offered has increased. , with a wide range of types, prices and qualities. To make it easier for people, especially consumers, to meet their daily needs. On the other hand, consumers are often targeted by marketers who consciously strive for maximum profit through campaigns and sales, often to the detriment of consumers. This is due to the low education, understanding and work ethic of traders. Also, there is no ethics in business. Therefore, there is a need to enact laws and regulations that can provide guarantees to all victims.